LiTaO3 phonon dispersion and ferroelectric transition calculated from first principles - Friedrich, Michael; Schindlmayr, Arno; Schmidt, Wolf Gero; Sanna, Simone (Physica Status Solidi B)
The phonon dispersions of the ferro‐ and paraelectric phase of LiTaO3 are calculated within density‐functional perturbation theory. The longitudinal optical phonon modes are theoretically derived and compared with available experimental data. Our results confirm the recent phonon assignment proposed by Margueron et al. [J. Appl. Phys. 111, 104105 (2012)] on the basis of spectroscopical studies. A comparison with the phonon band structure of the related material LiNbO3 shows minor differences that can be traced to the atomic‐mass difference between Ta and Nb. The presence of phonons with imaginary frequencies for the paraelectric phase suggests that it does not correspond to a minimum energy structure, and is compatible with an order‐disorder type phase transition.